Kuta Beach Festival Performance Based on Tourist Satisfaction - Natabella Widowati; Luh Yusni Wiarti; I Wayan Sukma Winarya Prabawa (Indonesian Journal of Applied and Industrial Sciences (ESA), 2025)
The existence of events at a tourist attraction can improve the image of a tourist destination. However, on the other hand, with the increasing number of tourism events held, there is a lack of evaluation of the event, so that the event is seasonal. This study was conducted at the Kuta Beach Festival held at Kuta Beach with the aim of determining the performance of the Kuta Beach Festival through tourist satisfaction. The type of data used is quantitative descriptive with a sample of 110 tourists who have visited the Kuta Beach Festival, the data obtained is processed using Importance Performance Analysis (IPA). The results of this study contain 6 statements in quadrant 1: a website related to the Kuta Beach Festival is available, information is available in print media, information is available in broadcast media, interesting performers, cleanliness of the venue is maintained and a parking area is available. These 6 statements are the main priorities for the organizers to evaluate.